Fabrication and properties of an injectable sodium alginate/PRP composite hydrogel as a potential cell carrier for cartilage repair. Issue 9 (23rd May 2019) - Gao, Xiang; Gao, Liyang; Groth, Thomas; Liu, Tianfeng; He, Dongning; Wang, Mingrui; Gong, Fan; Chu, Jiaqi; Zhao, Mingyan
Abstract: Three‐dimensional scaffolds like hydrogels can be employed as cell carriers for in vitro or in vivo colonization and have become a major research topic to replace damaged tissue. In the current study, a novel composite hydrogel composed of sodium alginate (SA) and platelet‐rich‐plasma (PRP) varying in blending ratios, cross‐linked with calcium ions, released from calcium carbonate‐D‐Glucono‐d‐lactone (CaCO3 ‐GDL) was successfully prepared. It was found that addition of PRP changed largely the physical properties and biological performance of the composite hydrogels, which was depending on the blending ratio. The gelation rate and swelling ratio of alginate hydrogels were significantly reduced by the addition of PRP, which produced also a more homogeneous gel structure. Field emission scanning electron microscopy (FE‐SEM) investigation confirmed the incorporation of PRP‐derived proteins in the hydrogel, where a porous structure with a pore size of 200–300 μm was found. On the other hand, an increase in surface roughness was observed after the addition of PRP. The compressive mechanical strength of SA/PRP composite hydrogel was enhanced in comparison to the pure SA gel. The composite hydrogels with the highest PRP content exhibited at a maximum compressive stress of 0.26 MPa a maximum strain of 55%, while the maximum compressive strain of pure SA hydrogels was only 45% at a stress of 0.08 MPa. It was also found that the in vitro degradation of the alginate gel was accelerated by the addition of PRP. In terms of cellular responses, all gels exhibited an excellent cytocompatibility. Indeed, the composite hydrogels supported bone marrow‐derived mesenchymal stem cells proliferation and their chondrogenesis with up‐regulation of chondrogenic marker genes Sox9 and Aggrecan. Overall, the present study suggests a great potential of SA/PRP composite hydrogels as cell carriers for cartilage tissue engineering.